AHEAD score — Long-term risk classification in acute heart failure. (1st January 2016) - Spinar, Jindrich; Jarkovsky, Jiri; Spinarova, Lenka; Mebazaa, Alexandre; Gayat, Etienne; Vitovec, Jiri; Linhart, Ales; Widimsky, Petr; Miklik, Roman; Zeman, Kamil; Belohlavek, Jan; Malek, Filip; et al.
Abstract: Background: The role of co-morbidities in the prognosis of patients hospitalized for AHF was examined using the AHEAD ( A — atrial fibrillation, H — haemoglobin < 130 g/l for men and 120 g/l for women (anaemia), E — elderly (age > 70 years), A — abnormal renal parameters (creatinine > 130 μmol/l), D — diabetes mellitus) scoring system. Methods: AHEAD — multicentre prospective Czech registry of AHF patients; GREAT registry — international cohort of AHF patients. Data from 5846 consecutive patients hospitalized for AHF (AHEAD registry; derivation cohort) were analysed to build the AHEAD score. Each risk factor of the AHEAD score was counted as 1 point. The model was validated externally using an international cohort of similar patients in the GREAT registry (6315). Results: Main outcome was one year all-cause mortality. The mean age of patients was 72 ± 12 years, with 61.6% of patients aged > 70 years; 43.4% were women. Atrial fibrillation was present in 30.7%, anaemia in 38.2%, creatinine > 130 mmol/l (abnormal renal parameters) in 30.1%, and diabetes mellitus in 44.0%. The mean AHEAD score was 2.1. In patients with AHEAD scores of 0–5, the one-year mortality rates were 13.6%, 23.4%, 32.0%, 41.1%, 47.7%, and 58.2%, respectively (p < 0.001), and the 90 month mortality rates were 35.1%, 57.3%, 73.5%, 84.8%, 88.0%, and 91.7%, respectively (p < 0.001). Conclusion: The AHEAD is a simple scoring system based on the analysis of co-morbidities for the estimation of the short and long term prognosis of patients hospitalized for AHF.